The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/app12147032
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Domain Transfer Learning for Fault Diagnosis with Small Samples

Abstract: The concept of deep transfer learning has spawned broad research into fault diagnosis with small samples. A considerable covariate shift between the source and target domains, however, could result in negative transfer and lower fault diagnosis task accuracy. To alleviate the adverse impacts of negative transfer, this research proposes an intra-domain transfer learning strategy that makes use of knowledge from a data-abundant source domain that is akin to the target domain. Concretely, a pre-trained model in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Zhanget al, [26] have suggested IBSA_Net: A network that uses small samples and transfer learning to identify tomato leaf diseases. The paper presented the provided IBSA_Net, a network for identifying tomato leaf diseases that uses small sample data and transfer learning together with the Shuffle Attention method to improve feature representation.…”
Section: Literature Surveymentioning
confidence: 99%
“…Zhanget al, [26] have suggested IBSA_Net: A network that uses small samples and transfer learning to identify tomato leaf diseases. The paper presented the provided IBSA_Net, a network for identifying tomato leaf diseases that uses small sample data and transfer learning together with the Shuffle Attention method to improve feature representation.…”
Section: Literature Surveymentioning
confidence: 99%
“…To address these challenges, various researchers have devised methods to improve the accuracy of diagnosis by learning fault features with limited training data. Specifically, these methods can be summarized as transfer learning [17][18][19], data enhancement [20][21][22], meta learning [23][24][25], and metric learning [26][27][28][29]. Some studies on small sample fault diagnosis have been published in the field of mechanical fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on small sample fault diagnosis have been published in the field of mechanical fault diagnosis. Zhang et al [17] applied an intra-domain transfer learning strategy to fault diagnosis. Based on transfer learning, Dong et al [19] applied the diagnostic knowledge learned from simulation data to real scenarios.…”
Section: Introductionmentioning
confidence: 99%